Identification of mangrove species based on substrate characteristics in Borimasunggu Village, Labakkang District, Pangkep Regency - Lukman Daris; Andi Nur Apung Massiseng; Jaya Jaya; Wahyuti Wahyuti (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
Mangroves are coastal ecosystems that have many benefits, including the ecological benefits of being a source of nutrients for marine life (aquatic biota) and a source of food for land biota. This study aimed to determine the species composition and community structure of mangrove vegetation based on the substrate type and the relationship between mangrove density and substrate texture in Borimasunggu Village, Labakang District. This research was carried out from July to August 2021 in the Borimasunggu Village, Labakkang District, Pangkep Regency. The research method is purposive random sampling which is divided into 3 stages. At each station, 3 transects/plots are determined. The study results found 3 mangrove species in Borimasunggu Village, Labakang District, based on the type of substrate, namely Rhizophora stylosa, Avicennia alba, and Sonneratia alba species. Relative Frequency (RFi) in Borimasunggu Sub-District, Labakang District, was found for all species equally, namely 33.33, the highest relative cover (RCi) was the species Rhizophora stylosa, which was 39.25, and the lowest Relative Coverage (RCi) was the mangrove species Sonneratia alba, which was 26,15. While the highest Significance Value (INP) is the mangrove species Rhizophora stylosa, which equals 148.66%, and the lowest Important Value (INP) is the mangrove species Sonneratia alba, which is equal to 70.59%. The highest relative density (RDi) was found in the mangrove species Rhizophora stylosa, which was 74.07% with a clay substrate type, followed by Avicennia alba 14.81% and Sonneratia alba 11.11% with a dusty clay substrate types.